Le jardin urbain de la Grande Bibliothèque : lieu ouvert et espace contesté - Louis Jacob (Projets de Paysage)
Based on a theoretical framework that address the question of mediality, i.e. the sedimentation and circulation processes, and the production of urban culture, this article reflects on the case of the urban park of the Grande Bibliothèque, in downtown Montréal. The article is also inquiring into the current transformations of the public space and the mundane phenomenology it entails. It is suggested that the urban park is opening out to the city, in the midst of a contradictory discursive space. The article illustrates how the artistic strategies, the pressure of the urban network, the development and revitalization projects in the nearby area, the practices and the memories of the place, all of those dimensions are heading for the “reframing” of the park as meaningfull structure, and of the whole spectacle of the city spreading inside and outside.